Synthesis of thiazolidin-4-ones and thiazinan-4-ones from 1-(2-aminoethyl)pyrrolidine as acetylcholinesterase inhibitors - Adriana M. das Neves; Gabriele A. Berwaldt; Cinara T. Avila; Taís B. Goulart; Bruna C. Moreira; Taís P. Ferreira; Mayara S. P. Soares; Nathalia S. Pedra; Luiza Spohr; Anita A. A. dE Souza; Roselia M. Spanevello; Wilson Cunico (Taylor & Francis Group, 2020)
The present study describes the synthesis of a novel series of thiazolidin-4-one and thiazinan-4-one using 1-(2-aminoethyl)pyrrolidine as amine precursor. All compounds were synthesised by one-pot three component cyclocondensation reaction from the amine, a substituted benzaldehyde and a mercaptocarboxylic acid. The compounds were obtained in moderate to good yields and were identified and characterised by 1H, 13 C, 2 D NMR and GC/MS techniques. The compounds also were screened for their in vitro acetylcholinesterase (AChE) activity in hippocampus and cerebral cortex on Wistar rats. The six most potent compounds have been investigated for their cytotoxicity by cell viability assay of astrocyte primary culture, an important cell of central nervous system. We highlighted two compounds (6a and 6k) that had the lowest IC50 in hippocampus (5.20 and 4.46 µM) and cerebral cortex (7.40 and 6.83 µM). These preliminary and important results could be considered a starting point for the development of new AChE inhibitory agents.